Primary site surgery for elderly patients with distant metastatic pancreatic neuroendocrine tumor: to do or not to do? - Zhang J (Dove Medical Press, 2019)
Jing Zhang,1 Chao-Sheng Peng,2,* Yu-Hong Tian3,*1Bachelor of Nursing, Special Medical Department, The Sixth Medical Center of People’s Liberation Army General Hospital (The Former Naval General Hospital of PLA), Beijing, People’s Republic of China; 2Special Medical Department, The Sixth Medical Center of People’s Liberation Army General Hospital (The Former Naval General Hospital of PLA), Beijing, People’s Republic of China; 3Bachelor of Nursing. Special Medical Department, The Sixth Medical Center of People’s Liberation Army General Hospital (The Former Naval General Hospital of PLA), Beijing, People’s Republic of China*These authors contributed equally to this workObjective: To investigate the effect of primary site surgery (PSS) on elderly patients (≥65 years) with pancreatic neuroendocrine tumor (pNET) distant metastasis.Patients and methods: We reviewed Surveillance Epidemiology and the End Results database for elderly patients with distant pNET from 1973 to 2015. The variables and survival outcomes of patients with PSS were compared with that of patients with no PSS. After propensity score matching, the survival outcome was compared again between the two groups. Multivariable Cox proportional hazard model was used to identify variables associated with cancer-specific and overall survival. Four sub-groups were divided according to the age and differentiation: 1) age 65–74 years+ well or moderately differentiated; 2) age ≥75 years+ well or moderately differentiated; 3) age 65–74 years+ poorly differentiated or undifferentiated; and 4) age ≥75 years+ poorly differentiated or undifferentiated. Cancer-specific survival was compared between the patients with and without PSS in the above each group.Results: A total of 210 elderly patients with distant pNET were finally confirmed. Of which, 148 patients did not undergo PSS, while 62 patients underwent PSS. Being female (p=0.049), locating on body/tail of pancreas (p=0.006), and well or moderately differentiated (p=0.032) were more likely received PSS. The patients underwent PSS had better survival outcomes both before and after propensity score matching. Multivariable Cox proportional hazard analysis proves PSS and higher histological grade to be protective and risk factors. PSS may improve cancer specific survival in patients of group 1), and no improvement was observed in patients of the other three sub-groups.Conclusion: Not all elderly patients with pNET distant metastasis could benefit from PSS. Patients aged 65–74 years with well or moderately differentiated may benefit from primary lesion surgery, but should be evaluated carefully. Prospective randomized controlled trials are worth performing.Keywords: primary site surgery, pancreatic neuroendocrine tumor, distant metastasis, elderly patients